Understanding the effect of pore size on the separation efficiency of methane-ethane mixtures using kinetic Monte Carlo simulation - Tan, Johnathan Shiliang (2022)
Although it is well acknowledged that pores are beneficial for enhancing adsorption, the effect of pore size on the selective adsorption of gas mixtures under subcritical condition is not known due to experimental challenges. To bridge this gap, the kinetic Monte Carlo method, which provides an accurate determination of chemical potential, was employed to understand the preferential adsorption of mixtures of methane and ethane on a graphitic plane, as well as graphitic pores sized between 1 and 4 nm. For a graphitic plane, results indicate high ethane selectivity of at least 80 mol % in the first adsorbed layer even at a low ethane mole fraction of 1 mol % in the gas phase, and the ethane proportion decreases further away to approach that of the bulk liquid. Regarding pore size, smaller ones provide higher ethane selectivity due to strong ethane-graphite affinity, but an extremely low pressure is required for desorption, which can be remedied with larger pores at the expense of a poorer ethane selectivity. The selectivity of ethane in the pore decreases as pressure increases, except at the onset of condensation. Therefore, in view of the trade-off between selectivity and amount adsorbed, adsorption can be performed at the pressure required for pore condensation rather than at the saturated vapor pressure.